The olfactory bulb – gateway for SARS-Cov-2? - Jovanović, Aleksandar; Niković, Jelena; Boban, Nikola; Pejin, Radoslav; Samardžić, Filip (Vojnosanitetski pregled, 2022)
Introduction. Anosmia and ageusia are one of the most common and characteristic symptoms of severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) infection, with a frequency of almost 50% in patients in Western countries. Hypotheses proposing that the virus potentially affects the central nervous system (CNS) are on the rise. One hypothesis suggests that the virus enters via nasal mucosa and then enters the olfactory bulb via cribriform plate, with further dissemination to the CNS. Case report. A 34-year-old female patient experienced the loss of the sense of smell and taste about two months before testing positive for SARS-Cov-2. Coronavirus disease 2019 (COVID-19) presented with minor pneumonia and worsening anosmia and ageusia. After treatment, the patient recovered well, but anosmia and ageusia appeared again, varying in intensity, and since February 2021, they have become persistent. The case was evaluated by an otorhinolaryngologist, pulmonologist, and finally, a neurologist. In the meantime, the patient tested negative for SARS-Cov-2 and received two doses of the Sputnik V vaccine. Brain magnetic resonance imaging (MRI) was performed, and it clearly showed severe bilateral olfactory bulb atrophy. The patient has had anosmia and ageusia up to this day, and future MRI follow-up is planned. Conclusion. Loss of sense of smell and taste may be a predictor of further CNS dissemination of the virus and possible neurological complications (which is still a subject of consideration). The olfactory bulb could be a gateway to COVID-19 intrusion into the CNS, and its atrophy could be an indicator of the process. Further investigation on this topic is required, including a wide application of MRI, in order to come to definite conclusions.
Keywords: ageusia; anosmia; atrophy; covid-19; olfactory bulb; magnetic resonance imaging